Assessing the impact of silvo-pastoral systems in the Colombian Amazon piedmont - Buritica, Alexander; Ngaiwi, Mary; Moreno, Manuel; Castro, Augusto; Gonzalez, Carolina; Urbani, Ilaria (2024)
This impact brief, part of the Impact Brief Series by the Performance, Innovation, and Strategic Analysis for Impact program of the Alliance of Bioversity International and CIAT, assesses the impact of Silvopastoral Systems (SPS) in the Caquetá region of the Colombian Amazon. Using a differences-in-differences (DiD) approach, the study, conducted several years after project completion, reveals improved livestock production, including increased cattle herd weight and higher income from animal sales and milk production, as well as reduced deforestation rates in SPS areas compared to control properties. These findings underscore SPS’s effectiveness in enhancing agricultural productivity while mitigating environmental degradation, offering valuable insights for sustainable livestock management.